Effects of trade and monetary policies on GDP growth and inflation in Vietnam using Vector autoregression model - Phan, Can Van.
Abstract (The study is interested in estimating the effects of trade and monetary policies on Gross Domestic Product (GDP) growth and Inflation in Vietnam using Vector Autoregression (VAR)/ Vector Error Correction Model (VECM). Quarterly economic data from 1995 to 2016 are used in the econometric models. Trade variable used is the sum of total exports and total imports, while monetary policy variables used are Interest Rate, measured as Treasury Bill Rate, and Money Supply. Having found evidence of long-run relationship between variables using the Johansen and Engle-Granger Tests, the VECM results show that there exists strong relationship between trade policies on GDP growth in Vietnam. The paper's findings show that a shock to Trade variable can explain substantial percentage of future movements in the GDP in the short run (one quarter ahead) and in the medium term (4 quarters ahead). Monetary policies, however, has minimal effects on the GDP growth. For inflation, measured using the Consumer Price Index (CPI), the econometric results also show a stronger link from the trade and monetary policy variables. The results show the importance of trade in the economic activity of Vietnam, as it becomes more open to the world economy. This is consistent with the current economic policies in Vietnam that is to develop business environment and opportunities for supporting trade).
June 2018
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Vector error correction model; Variance decomposition